2001
DOI: 10.1111/j.1365-2621.2001.tb08224.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Thermally Induced Inulin Gel

Abstract: Heated inulin solution undergoes a sol-gel transition during cooling and forms a white smooth gel under optimized conditions. The degree of gel formation is negatively related to hydrolysis of inulin during heating. Heating makes inulin soluble; overheating causes hydrolysis of dissolved inulin into smaller molecules. Using a 2-step model including a solubilization step and a hydrolysis of inulin step, we found that both steps follow pseudo first-order kinetics. Separate studies on initial rates of the solubil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The analysis of the hardness and shear stress values is in agreement with the results of the previous findings (Kim & Wang, 2001; Kim et al. , 2001).…”
Section: Resultssupporting
confidence: 92%
“…The analysis of the hardness and shear stress values is in agreement with the results of the previous findings (Kim & Wang, 2001; Kim et al. , 2001).…”
Section: Resultssupporting
confidence: 92%
“…It is possible that in MPA samples, the structure of the MP was thickened due to the high INL concentration, because the system had enough particles and/or sufficient molecular INL chain density to reach a critical crowding effect. [4,30] This speculation is in agreement with the microstructure observed in INL-EVOO-based MP samples, [37] where amylose/amylopectin form a rigid matrix in which I particles are trapped. Guggisberg et al [38] showed that even though firmness and creaminess of low-fat set yogurt increased with both INL and fat content, the highest level of INL considered (4%) was not enough to imitate the whole-milk yogurt.…”
Section: Influence Of Composition and A Freeze/thaw Cycle On Instrumesupporting
confidence: 83%
“…EVOO (Carbonell, Sevilla, Spain) was chosen for addition to the MP. Kappa-carrageenan (κ-C) ( 30). Additional samples without added ingredients (0:0 control), with 60 g/kg added I alone (60:0) and with 60 g/kg added EVOO alone (0:60) were also prepared for each type of MP and processing condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the environmental conditions and fibre concentration, inulin can form gels, consequently modifying the rheological behaviour of the systems to which it is added (Kim and Wang 2001; Kim et al. 2001).…”
Section: Introductionmentioning
confidence: 99%